Towards sustainable ocean governance: A call for blue climate action in international development - Ina Lehmann; Michael Siebert; Maximilian Högl; Anna-Katharina Hornidge (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
The ocean is vital for life on earth and yet it is under serious threat from climate change and resource overexploitation. Environmental change in the ocean significantly undermines human livelihoods, especially in the developing and least developed countries where people are particularly vulnerable to climate change-related losses and damages. This Briefing Paper outlines challenges that people, development cooperation and policy face and suggests ways forward for sustainable ocean governance through sustainable resource use, comprehensive risk management and enhanced climate action. Life in the ocean is threatened in various ways by human activities. Climate change, as one severe consequence, leads to ocean warming and ocean acidification putting complex ecosystems and their sensitive species in danger. Such climatic impacts are exacerbated by pollution, especially plastic, and the overharvesting of many marine species. As a result of the confluence of these developments, many local coastal communities lose their livelihoods. At the same time, climate change increasingly threatens coasts through sea level rise, salinisation and growing frequencies of extreme weather events, such as floods and storms. This puts the 2.6 billion people living at or near the coasts at high risk; low-altitude small islands are expected to become uninhabitable within the next decades if current global warming trajectories continue. Furthermore, the ocean contributes to climate change mitigation because marine ecosystems absorb CO2. In response to these challenges, there is a need for sustained awareness raising on the importance of the ocean for development as well as for the need of enhanced international cooperation for joint action. Conscious politics, substantial action and financial resources are needed at multiple levels of governance, from empowering local stakeholders to developing locally sound solutions to political guidance through national and international policy-making processes. From a development policy angle, this Briefing Paper specifically suggests that current climate and biodiversity policy processes pay enhanced attention to the ocean under climate change, pollution and overexploitation stress. This should be guided by the overarching vision of a sustainable blue economy. More concrete reform needs are a stronger focus on responsible stakeholder inclusion at all levels in ocean governance in general, ranging from individual households to communities, private sector and governments; expansion of marine protected areas and promotion of marine and coastal nature-based solutions to complement sustainable blue economies while ensuring their inclusive and rights-based governance; support for sustainable small-scale fisheries and promotion of eco-friendly mariculture and aquaculture; expansion of the reach of the UNFCCC's Nairobi Work Programme and the Warsaw International Mechanism for Loss and Damage (WIM) to oceans and coasts; and support for radical decarbonisation pathways and a carbon-neutral blue economy.
Keywords: 330